AGR702: Advanced Crop Production / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (2023)
The course covers the use of advanced tools in plantation crop production and the concept of precision agriculture. The knowledge of crop physiology and integrated farming will be applied for optimizing the land use and pro